Canada China Relations under Political Tensions: A look through the lens of International Trade and Investmen - Yecong, Liu (Université d'Ottawa | University of Ottawa, 2022)
China-Canada relations have a long history. 2020 represented the 50th anniversary of the establishment of diplomatic relations between China and Canada. Economic collaboration has been an important topic of bilateral exchange for decades. Yet, there has been no shortage of discussion of the deterioration of the relationship in recent years. The goal of this major research paper is to analyze the direction of the China-Canada relationship from a trade and investment perspective. The years 2018 and 2019 mark the lowest point in this relationship, but the seeds of the deeper causes were planted in the early years of diplomatic relations. The reason for this is the fundamental differences between the two countries in their understanding of the rule of law, human rights, and diplomatic approaches. These disagreements also had an impact on investment and trade, and these effects were undeniably passed on to the Canadian society itself. Analyzing these implications, this paper concludes that the future of the relationship, from a Canadian perspective, will focus on two areas: continued engagement with China to maintain collaboration on areas of common interest (e.g., climate change actions, two-way trade and investment cooperation) and active engagement with similarly minded Indo-Pacific partners to diversify trade and investments away from China.